숙지황 농축액 첨가 초콜릿의 품질 특성 및 항산화성 - 김초롱(Cho Rong Kim); 박효정(Hyo Jeong Park); 오혜림(Hye Lim Oh); 나용근(Yong Geun Na); 도은수(Eun Soo Doh); 윤준화(Jun Hwa Yoon); 심은경(Eun Kyung Shim); 김미리(Mee Ree Kim) (東아시아食生活學會誌, 2012)
The purpose of this study was to evaluate the quality characteristics and antioxidant activity of chocolate added with Rehmannia Radix Preparata (R. Radix Preparata) concentrate (0, 3, 6 and 9%). As the amount of R. Radix Preparata concentrate increased, water content significantly. The pH of chocolate decreased significantly as R. Radix Preparata concentrate increased, but the acidity of chocolate increased. Sugar concentration and reducing sugar contents also increased according to the amount of R. Radix Preparata concentrate. The L(lightness), a(redness) and b(yellowness) values significantly decreased as R. Radix Preparata concentrate increased. However, texture was not significantly different among the treatments. As the amount of R. Radix Preparata concentrate increased, DPPH radical scavenging and hydroxyl radical scavenging activities increased. In the results of the sensory evaluation, scores of color, taste, flavor, texture, and overall acceptability were the highest in chocolate added with 6% R. Radix Preparata concentrate. From these results, it was suggested that the optimum addition amount of R. Radix Preparata concentrate to chocolate is 6%.